Comparison of Piezosurgery Devices and the Use of Rotatory Devices for the Extraction of Impacted Mandibular Third Molars - Sheffali Walia; Dinesh Verma; Shallu Bansal; Smita Sutar; Asheen Gupta; Kapil Kardwal (Wolters Kluwer Medknow Publications, 2024)
The present study aimed to examine the extraction of impacted mandibular third molars by using rotatory and piezosurgery equipment. Twenty-five patients of both genders who required surgery to remove their third molars were split into two groups (control group and research group). In the surgical extraction of the impacted mandibular third molar, in the study group, a piezotome was used to remove the bone, while in the control group, a bur was used. Patients' acceptance of bone cutting, the length of the operation, discomfort and bleeding during the procedure, postoperative pain, swelling, trismus, and wound healing were evaluated. A statistically insignificant difference was observed for age and difficulty index. The intraoperative bleeding was similar in both groups. Both the groups tolerated the bone cutting well, with slightly better values for the piezo group. Based on Pederson's difficulty index, the scores of difficulty of extraction of the impacted tooth were measured between the groups. The slight difficulty was observed in 9 (36%) each in the study group and control group. The moderate difficulty in 14 (56%) of control group and 15 (60%) of study group. Severe difficulty was found among 2 (8%) in the control group and 1 (4%) in the study group. The difference was not significant (P > 0.05). Intraoral bleeding was moderately seen in 25 in both groups. Among the study and control groups respectively no intraoperative pain was seen in 14 and 16, mild intraoperative pain in 11 and 7, and moderate intraoperative pain in 0 and 2. Among group I and II acceptance to bone cutting was comfortably seen in 24 and 23, bearable in 1 and 2 respectively. The difference was not significant (P > 0.05). Piezosurgery and bur were comparable in evaluating patient acceptance, intraoperative duration, intraoperative bleeding and pain, postoperative pain, edema, trismus, and wound healing.